The Wiley Blackwell Encyclopedia of Health, Illness, Behavior, and Society 2014
DOI: 10.1002/9781118410868.wbehibs256
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and Marital Status

Abstract: Marriage is a social institution and its effects on mental health vary across societies. In societies which emphasize marriage, being married is related to lower depression, lower anxiety, lower suicide risk, and lower substance abuse, on average. Two models explain the relationship between mental health and marital status: causation and selection. Selection models propose that healthy and socially desirable people are more likely to become and stay married. In causation models, marriage confers benefits direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…Indirectly, these can cause more anxiety to the patients. Some literature found a significant association between marital status and anxiety [28]; however, our study found no significant association in line with some other literature [11]. Same goes to religion factor as studies have shown that anxiety was associated with religion in which religious belief has significantly reduced anxiety or patient's stress and reduced the avoidance coping thus support in reducing stress [29].…”
Section: Discussionsupporting
confidence: 81%
“…Indirectly, these can cause more anxiety to the patients. Some literature found a significant association between marital status and anxiety [28]; however, our study found no significant association in line with some other literature [11]. Same goes to religion factor as studies have shown that anxiety was associated with religion in which religious belief has significantly reduced anxiety or patient's stress and reduced the avoidance coping thus support in reducing stress [29].…”
Section: Discussionsupporting
confidence: 81%
“…Covariates were selected based on previous literature indicating that these variables are associated with mental health (34)(35)(36)(37)(38)(39)(40). The following six covariates were employed: age (<65, 65-74, >74), province (Alberta, British Columbia, Manitoba, New Brunswick, Newfoundland and Labrador, Nova Scotia, Ontario, Prince Edward Island, Quebec, and Saskatchewan), education (less than post-secondary degree/diploma and post-secondary degree/diploma), household income (<$50,000 a year; ≥$50,000, <$100,000 a year; ≥$100,000, <$150,000 a year; ≥$150,000 a year), marital status (married or common law; not married/not common-law: single, never married, never lived with partner, widowed, divorced, or separated), and ethnicity [other (nonwhite), white only, to account for less than five cell counts].…”
Section: Covariatesmentioning
confidence: 99%
“…However, patients are still at risk of complications and side effects, especially urinary incontinence and erectile dysfunction (4). When these side effects occur among younger patients (e.g., 40 to 65 years of age), they violate expectations regarding urinary and erectile function age norms and often negatively impact the psychological well-being of patients (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, marriage has an effect on mental health across societies. It lowers depression, anxiety, suicide risk, and substance abuse ( Spiker, 2014 ). The present study strengthens the role of social networks such as marital relationships in understanding health behaviors and health outcomes among the population ( Christakis and Fowler, 2008 ; Molloy et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%